FEATURES CLINICAL COURSE OF CHICKENPOX (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The report presents clinical and epidemiological data from the analysis of case histories of 60 patients with chickenpox in adults and children. The comparative frequency of occurrence of the main symptoms of chickenpox in adult patients and children, including newborns, is given. The features of the course of the disease in adults were established: the prevalence of severe forms (up to 70%) with prodromal symptoms, febrile fever, abundant large rash with slow reverse development and itching of the skin. The clinical symptoms of chickenpox in newborns are described, depending on the timing of chickenpox disease in pregnant women before delivery. There was a severe course of chickenpox in newborns, the possibility of developing generalized forms with damage to the visceral organs and the central nervous system, with the disease of a pregnant woman 3-4 days before delivery. Data on the treatment and tactics of a doctor for the prevention of chickenpox are presented.